Ecological Studies of Cestode Parasites of Some Marine Fishes along the Raigad coast (M.S) India - Yogesh Reddy, Sunil Patil, Vasant Dongare, Hemlata Chaudhari (Recent Research in Science and Technology, 2009)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â This communication deals with ecological studies of cestode parasites of some marine fishes along the Raigad coast (M.S) India, over a period of one year (June to December 2006 and January to May 2007). The study highlights at establishing the magnitude of parasitization in different fishes as well as quantifying the host specificity of the parasites and their fish hosts. Fish samples were collected from main landing beaches of Raigad coast: Alibag, Borli, Murud, Dighi and Shrivardhan. The fish sample (Host) examined for parasites included: Rastrelliger kanagurata, Dasyatis bleekeri, Dasyatis walga, Aetomylaeus nichoffii, Chiloscyllium palgiosum, Mobula mobular, Carcharihinus dussumeri and Rhynchobatus djeddensis. This study has revealed that out of 8 fishes examined only 5 species were infected with parasites. Dasyatis bleekari infected with Acanthobothrium and Rhinebothrium; Dasyatis walga infected with Tetragonacephalum and Nybelina: Aetomylaeus nichoffii infected with Hexacanalis and Tylocephalum; Chiloscyllium plagiosum infected with Phyllobothrium: Rhynchobatus djeddensis infected with Tetragonacephalum, out of the 5 species Dasyatis bleekari was the most heavily infected increase with age (size) especially in Aetomylaeus nichoffii where very young fish were rarely infected where asÃ‚Â Ã‚Â Ã‚Â Ã‚Â adultÃ‚Â were heavily infected.